Acute Exacerbations and Lung Function Loss in Smokers with and without Chronic Obstructive Pulmonary Disease - Dransfield, Mark T.; Kunisaki, Ken M.; Strand, Matthew J.; Anzueto, Antonio; Bhatt, Surya P.; Bowler, Russell P.; Criner, Gerard J.; Curtis, Jeffrey L.; Hanania, Nicola A.; Nath, Hrudaya; Putcha, Nirupama; Roark, Sarah E.; et al. (American journal of respiratory and critical care medicine, 2017)
Acute exacerbations of chronic obstructive pulmonary disease (COPD) increase the risk of death and drive healthcare costs, but whether they accelerate loss of lung function remains controversial. Whether exacerbations in subjects with mild COPD or similar acute respiratory events in smokers without airflow obstruction affect lung function decline is unknown. To determine the association between acute exacerbations of COPD (and acute respiratory events in smokers without COPD) and the change in lung function over 5 years of follow-up. We examined data on the first 2,000 subjects who returned for a second COPDGene visit 5 years after enrollment. Baseline data included demographics, smoking history, and computed tomography emphysema. We defined exacerbations (and acute respiratory events in those without established COPD) as acute respiratory symptoms requiring either antibiotics or systemic steroids, and severe events by the need for hospitalization. Throughout the 5-year follow-up period, we collected self-reported acute respiratory event data at 6-month intervals. We used linear mixed models to fit FEV decline based on reported exacerbations or acute respiratory events. In subjects with COPD, exacerbations were associated with excess FEV decline, with the greatest effect in Global Initiative for Chronic Obstructive Lung Disease stage 1, where each exacerbation was associated with an additional 23 ml/yr decline (95% confidence interval, 2-44; P = 0.03), and each severe exacerbation with an additional 87 ml/yr decline (95% confidence interval, 23-151; P = 0.008); statistically significant but smaller effects were observed in Global Initiative for Chronic Obstructive Lung Disease stage 2 and 3 subjects. In subjects without airflow obstruction, acute respiratory events were not associated with additional FEV decline. Exacerbations are associated with accelerated lung function loss in subjects with established COPD, particularly those with mild disease. Trials are needed to test existing and novel therapies in subjects with early/mild COPD to potentially reduce the risk of progressing to more advanced lung disease. Clinical trial registered with www.clinicaltrials.gov (NCT 00608764).